Integration of Multivariable Polynomials with Hypergeometric Functions: Analytical Solutions - Purohit, Urmila; Sharma, Aparna (Journal of Educational Research and Policies, 2026)
The purpose of this paper is to establish some certain integrals involving G-function and multivariable polynomial as product. Integrals are obtained by combining the products of first- and second-class general polynomials with the g-function of one variable and n- variables.